Reviews and notices - Göran Kjellmer; Ann-Marie Svensson; Monica Malm; Paul Goulding; Ronald Paul; Nathaniel Chase; Alan McGee; Edelgard Biedermann; Stefan Neuhaus; Hans-Roland Johnsson; Karl-Anders Arvidsson; Gabriella Villagrán Backman (Moderna Språk)
Includes the following reviews: pp. 100-102. Göran Kjellmer. Hill, J. & Lewis, M. (eds), Dictionary of Selected Collocations.